Biochemistry and use of soybean isoflavones in functional food development. Issue 12 (3rd July 2020) - Hu, Chengshen; Wong, Wing-Tak; Wu, Runyu; Lai, Wing-Fu
Abstract: Soybeans and their food products exist in the market in various forms, ranging from crude oils and bean meals to nutritious products (e.g. soy milk powers). With the availability of technologies for mass production of soy products and for enrichment of soy components (e.g. phospholipids, saponins, isoflavones, oligosaccharides and edible fiber), the nutritional values of soy products have been enhanced remarkably, offering the potential for functional food development. Among different bioactive components in soybeans, one important component is isoflavones, which have been widely exploited for health implications. While there are studies supporting the health benefits of isoflavones, concerns on adverse effects have been raised in the literature. The objective of this article is to review the recent understanding of the biological activities, adverse effects, and use of isoflavones in functional food development.